KNOWLEDGE AND ATTITUDES TOWARD STROKE PREVENTION AMONG ELDERLY PATIENTS WITH HYPERTENSION (Vietnam Journal of Community Medicine, 2026)
Objective: To assess the knowledge and attitudes toward stroke prevention among elderly patients with hypertension and to identify factors associated with positive attitudes.Subjects and methods: A cross-sectional study was conducted on 353 elderly patients diagnosed with hypertension and managed at Thanh Thuy Medical Center, Phu Tho province, from October 2024 to March 2025. Statistical analyses were performed using SPSS 26.0 software, with a significance level of p < 0.05.Results: Among 353 participants (median age: 70 years), 34.3% demonstrated good knowledge, while 87.8% showed positive attitudes toward stroke prevention. Logistic regression revealed that living with family (OR = 18.5; 95% CI: 3.76-91.23; p < 0.001), having good knowledge (OR = 7.80; 95% CI: 2.56-23.82; p < 0.001), previous exposure to stroke prevention media (OR = 6.49; 95% CI: 2.16-19.53; p = 0.001), and higher educational level (OR = 0.078; 95% CI: 0.03-0.21; p < 0.001) were independent predictors of positive attitudes.Conclusion: Most elderly hypertensive patients had positive attitudes but limited knowledge about stroke prevention. Educational level, living with family, prior exposure to stroke-related information, and good knowledge were key determinants of positive attitudes. Strengthening family-based education and public communication is essential to enhance stroke prevention awareness in this high-risk population.
Keywords: Stroke prevention, hypertension, elderly, knowledge, attitude.